Inclusive Character Education: A Critical Review of the Literature on Teachers' Experiences in Managing Classrooms with Diverse Learning Needs - Muhamad Rif'an (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to critically examine teachers' experiences in building character education in inclusive classes inhabited by students with diverse learning needs. Using a qualitative approach with a literature review method, this study analyzed national and international scientific articles published between 2021 and 2025. Thematic analysis was used to identify experiences, strategies, and supporting and inhibiting factors in the implementation of inclusive character education. The results of the study indicate that teachers act as facilitators of values ​​and moral agents who shape students' character through contextual approaches, local culture, habituation, and collaborative projects. The success of implementation is greatly influenced by structural support, a conducive school culture, and the involvement of the educational community. On the other hand, limited resources, lack of teacher training, and low parental involvement are the main obstacles. These findings emphasize the importance of reflective pedagogical practices, adaptive internal policies, and cross-sector collaboration as the foundation for inclusive and transformative character education.